Can screening 4–5 year olds accurately identify children who will have teacher-reported mental health problems when children are aged 6–7 years?. (June 2014) - Sawyer, Alyssa CP; Chittleborough, Catherine R; Lynch, John W; Baghurst, Peter; Mittinty, Murthy N; Kaim, Amy LE; Sawyer, Michael G
Objective: To assess the screening accuracy of information obtained from parents of 4–5-year-old children for the purpose of identifying the children who have teacher-reported mental health problems when they are aged 6–7 years. Method: The study used data from the Longitudinal Study of Australian Children (LSAC) obtained when children were aged 4–5 years and 6–7 years. The level of children's mental health problems was assessed using the Strengths and Difficulties Questionnaire (SDQ) completed by parents when children were aged 4–5 years and by teachers when children were aged 6–7 years ( n =2163). When children were aged 4–5 years, parenting skills were assessed using three questionnaires developed for the parent-completed LSAC questionnaire and maternal mental health was assessed using the Kessler Psychological Distress Scale (K6). Results: When the level of parent-reported childhood mental health problems at 4–5 years old was used to identify children with teacher-reported mental health problems (i.e. a score in the "abnormal" range of the teacher-reported SDQ Total Difficulties Scale) when the children were aged 6–7 years, sensitivity was 26.8%, positive predictive value was 22.8%, and specificity was 92.9%. The addition of further information about the characteristics of children and their parents made only a small improvement to screening accuracy. Conclusions: Targeted interventions for preschool children may have the potential to play an important role in reducing the prevalence of mental health problems during the early school years. However, current capacity to accurately identify preschoolers who will experience teacher-reported mental health problems during the early school years is limited.